2014
DOI: 10.3389/fcimb.2013.00114
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of intestinal epithelial cell function by the cell contact-dependent type III secretion systems of Vibrio parahaemolyticus

Abstract: Vibrio parahaemolyticus elicits gastroenteritis by deploying Type III Secretion Systems (TTSS) to deliver effector proteins into epithelial cells of the human intestinal tract. The bacteria must adhere to the human cells to allow colonization and operation of the TTSS translocation apparatus bridging the bacterium and the host cell. This article first reviews recent advances in identifying the molecules responsible for intercellular adherence. V. parahaemolyticus possesses two TTSS, each of which delivers an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 113 publications
(208 reference statements)
0
39
0
Order By: Relevance
“…We created mutants lacking one or more of the 3 previously described V. parahaemolyticus adhesin-encoding genes ( mam7 , mshA1 and vpadF ) (Boyd, 2014) that have been implicated in T3SS1-killing to test whether they interact with sulfated compounds and contribute to the sulfation-dependent adhesion of the pathogen to host cells. MshA1 has been reported to bind both sulfated and non-sulfated glycans, while MAM7 and VpadF are reported to bind fibrinogen and/or fibronectin.…”
Section: Resultsmentioning
confidence: 99%
“…We created mutants lacking one or more of the 3 previously described V. parahaemolyticus adhesin-encoding genes ( mam7 , mshA1 and vpadF ) (Boyd, 2014) that have been implicated in T3SS1-killing to test whether they interact with sulfated compounds and contribute to the sulfation-dependent adhesion of the pathogen to host cells. MshA1 has been reported to bind both sulfated and non-sulfated glycans, while MAM7 and VpadF are reported to bind fibrinogen and/or fibronectin.…”
Section: Resultsmentioning
confidence: 99%
“…In immune-competent individuals, the illness is self-limiting and resolves itself within about 3 days. The symptoms include diarrhea with abdominal cramps, nausea, vomiting, low-grade fever, and occasional bloody diarrhea [8][9][10]. In immunocompromised individuals and those with certain underlying medical conditions, such as liver disease, diabetes, and cancer, V. parahaemolyticus can cross the intestinal barriers and reach the blood vessels, which leads to systemic spread of bacteria, a condition known as septicemia.…”
Section: Parahaemolyticusmentioning
confidence: 99%
“…Adhesion occurs when adhesive molecules expressed on the bacterial surface bind to host surface receptors. Bacterial adhesins range from single monomeric proteins to multimeric complexes that may work in concert to yield a multivalent interaction between pathogen and host [8,34]. The following section will discuss in more detail the contribution of the capsular polysaccharide, the mannose-sensitive hemagglutinin (MSHA) Type IV pilus, and the multivalent adhesion molecule 7 (MAM7) to bacteria-host binding and their implications for pathogenicity.…”
Section: Adhesinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The completed genome sequence of V. parahaemolyticus RIMD2210633, an O3:K6 serotype associated with pandemic disease, demonstrated the presence of two type III secretion systems (T3SS-1 and T3SS-2), one on each chromosome, which led to the identification of several effector proteins associated with inflammatory diarrhea (6)(7)(8). Studies have shown that T3SS-2 is the major contributing factor to enterotoxicity and that inflammatory diarrhea and intestinal epithelium cell disruption are dependent upon a functional T3SS-2 (9)(10)(11)(12).…”
mentioning
confidence: 99%